The puzzle with increasing money demand: Evidence from a cross-section of countries - Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2004)
The ratio of money demand to GDP may increase with portfolio demand, monetization, and a deeper division of labor. Using a cross-section approach to money demand for 126 countries this study shows that the share of agriculture, life expectancy at birth, openness, and trust in the banking system capture a good deal of these influences. Once these variables are included, GNP per head negatively impacts on the ratio of money demand to GDP, which is in line with the standard result by Tobin and Baumol.
Keywords: E41; C21; 330